Negative electrode protection layer and preparation method thereof, lithium battery negative electrode and lithium battery
The zeolite molecular sieve and the double crosslinked hybrid layer of polymer fluoropolymer prepared by electrospinning technology are used as the protective layer of metal lithium negative electrodes, which solves the problem of poor stability of metal lithium negative electrodes under high area capacity and achieves high ratio Energy lithium batteries have uniform deposition and long life.
Patent Information
- Application Number
- CN202510035326.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-02-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The metal lithium anode has poor stability, lithium dendrites growth and safety hazards under high area capacity. The existing protective layer is difficult to meet the requirements in high-specific energy lithium battery applications.
A double crosslinked hybrid layer prepared by electrostatic coaxial convection spinning is used as the negative electrode protective layer to react in situ to form a protective layer after contacting metal lithium.
The protective layer has high modulus and excellent flexibility, which can effectively isolate lithium metal and electrolyte, achieve uniform deposition of lithium ions, inhibit the growth of dendrites, and improve the circulation performance and life of lithium metal batteries.
Smart Images

Figure CN119419218A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a negative electrode protective layer and a preparation method thereof, a lithium battery negative electrode and a lithium battery. Background Art
[0002] In recent years, with the rapid development of electric vehicles, research on high energy density lithium-ion batteries (LIBs) has increased. Among different cathode candidate materials, metallic lithium has a high theoretical specific capacity (3860 mAh g -1 ) and the lowest redox potential (-3.04 V). However, the poor reversibility of metallic lithium anodes and the growth of lithium dendrites have hindered their commercial application. Due to its active chemical properties, metallic lithium can react with solvents and lithium salts in organic electrolytes to form a thin solid electrolyte interface (SEI) layer on the surface to prevent continuous side reactions. However, the fragile SEI film cannot withstand the huge volume changes during charge and discharge, and the cracks in the SEI will aggravate the parasitic reactions between fresh lithium metal and the electrolyte, resulting in a sharp decrease in the Coulombic efficiency (CE) and cycle life of lithium metal batteries (LMBs). In addition, the inhomogeneity of the SEI anode film in structure and composition can lead to uneven lithium ion deposition, resulting in lithium dendrites and even safety hazards. These problems will accelerate when the LMB operates at higher current density and areal capacity.
[0003] To further solve the numerous problems existing in current metallic lithium anodes, it is meaningful to try to design stable and functional protective layers to obtain uniform lithium stripping / plating at high areal capacity. So far, some effective solutions have been proposed to obtain alternative protective layers, such as in situ formation of inorganic layers by electrolyte engineering, and ex situ formation of artificial protective layers. However, the in situ formed SEI layer has a low capacity at over 4 mAh / cm 2 It is difficult to suppress large volume changes at high areal capacities, leading to SEI degradation and electrolyte consumption. In recent years, various protective layers such as inorganic materials, organic polymers, and inorganic-organic hybrid layers have been developed to effectively strengthen the lithium-electrolyte interface and improve electrochemical performance. However, for high-energy LMBs above 500 Wh / kg, few can meet the requirements of soft-pack batteries under practical conditions.
[0004] Therefore, in order to produce high-energy-density lithium batteries, it is necessary to rationally design a stable, high-area-capacity artificial protective layer for the negative electrode of lithium metal batteries under realistic conditions, which is an urgent problem to be solved in this field. Summary of the invention
[0005] The purpose of the present invention is to provide a negative electrode protective layer and a preparation method thereof, a negative electrode and a lithium battery, so as to solve the problem of poor stability of the negative electrode of a lithium metal battery.
[0006] The purpose of the present invention can be achieved through the following technical solutions: In a first aspect, the present invention provides a negative electrode protective layer, which is a double cross-linked hybrid layer prepared by electrostatic coaxial convection spinning of a zeolite molecular sieve dispersion and a high molecular fluorine-containing polymer solution, and in-situ reaction after contact with a metal lithium negative electrode.
[0007] Furthermore, the thickness of the negative electrode protective layer is 3-6 μm.
[0008] Furthermore, the zeolite molecular sieve dispersion includes zeolite molecular sieve and a first solvent, and the first solvent is at least one of N-methylpyrrolidone, propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate; The zeolite molecular sieve is at least one of ZSM-5, titanium silicalite molecular sieve, SAPO-34, MCM-22, MOR, SSZ-13, MCM-48, SAPO-5, and SBA-15.
[0009] Furthermore, the mass ratio of the zeolite molecular sieve to the first solvent is 10-25:75-90.
[0010] Furthermore, the high molecular fluorine-containing polymer solution includes a high molecular fluorine-containing polymer and a second solvent; the second solvent is N,N-dimethylformamide, dimethyl sulfoxide, N,N-dimethylacetamide, triethyl phosphate, acetone, and dioxane; the high molecular fluorine-containing polymer includes at least one of PTFE (polytetrafluoroethylene), FEP (fluorinated ethylene propylene copolymer), PFA (fusible polytetrafluoroethylene), PVDF (polyvinylidene fluoride) and EPTFE (expanded polytetrafluoroethylene).
[0011] Furthermore, the mass ratio of the high molecular weight fluorine-containing polymer to the second solvent is 2-5:95-98.
[0012] In a second aspect, the present invention provides a method for preparing a negative electrode protective layer, comprising the following steps: Under a protective atmosphere, stirring the zeolite molecular sieve and the first solvent at room temperature to obtain a zeolite molecular sieve dispersion, and stirring the high molecular weight fluorine-containing polymer and the second solvent at room temperature to obtain a high molecular weight fluorine-containing polymer solution; The zeolite molecular sieve dispersion and the high molecular weight fluorine-containing polymer solution are electrostatically coaxially spun on the lithium surface. After the spinning is completed, vacuum drying is performed to obtain an in-situ formed negative electrode protective layer.
[0013] Furthermore, the stirring speed is 300-800 rpm, and the time is 2-4 h.
[0014] Furthermore, the conditions for electrostatic coaxial convection spinning are: The electrospinning spray solution feed rate of zeolite molecular sieve dispersion was 0.4 mL·h -1 ~0.6 mL·h -1 , the applied voltage is 22-25kV, the distance between the spinneret tip and the current collector is 15cm-20cm, the temperature is 26℃, and the relative humidity is 35%; The electrospinning rate of the fluorinated polymer solution was 0.6 mL·h. -1 ~ 0.9 mL·h -1 , the applied voltage was 25-28 kV, the distance between the spinneret tip and the current collector was 15 cm~20 cm, the temperature was 26°C, and the relative humidity was 35%.
[0015] Furthermore, the protective atmosphere is formed by a protective gas, and the protective gas is one of an inert gas and nitrogen.
[0016] In a third aspect, the present invention provides a negative electrode for a lithium battery, wherein the negative electrode for the lithium battery comprises the negative electrode protective layer described above.
[0017] In a third aspect, the present invention provides a lithium battery, comprising the above-mentioned lithium battery negative electrode.
[0018] Beneficial effects of the present invention: 1) The metal lithium negative electrode protection material (derived from zeolite molecular sieve and high molecular weight fluorinated polymer) provided by the present invention has a high modulus and excellent flexibility, and is applied to the negative electrode of lithium metal to generate a high-performance lithium-philic artificial hybrid protection layer, which can isolate lithium metal and electrolyte, realize the protection of lithium metal electrode and the uniform deposition of lithium ions, and inhibit the growth of dendrites. The lithium metal electrode has high ion conductivity and good stability, which can extend the life of lithium metal batteries and improve the cycle performance of lithium metal batteries; 2) The preparation method of the metal lithium negative electrode protective layer provided by the present invention is simple, has good repeatability, is low in cost, and can be prepared on a large scale. The obtained electrode material can be directly used as a high-energy lithium metal battery with no dendrites and high coulombic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The present invention will be further described below in conjunction with the accompanying drawings.
[0020] Figure 1 is an electron microscope image of the surface of the metal lithium negative electrode protective layer obtained in Example 3 of the present invention; Figure 2 This is a cross-sectional electron microscope image of the metal lithium negative electrode protective layer obtained in Example 3 of the present invention. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] The invention provides a metal lithium negative electrode protection material and a preparation method thereof, as well as a corresponding lithium metal battery negative electrode and a high specific energy lithium metal battery.
[0023] The technical solution, its implementation process and principle will be further explained as follows.
[0024] In a first aspect, the present invention provides a negative electrode protective layer, which is a double cross-linked hybrid layer prepared by electrostatic coaxial convection spinning of a zeolite molecular sieve dispersion and a high molecular fluorine-containing polymer solution, and in-situ reaction after contact with a metallic lithium negative electrode.
[0025] In some specific embodiments, the thickness of the negative electrode protection layer is 3-6 μm.
[0026] In some specific embodiments, the zeolite molecular sieve dispersion includes zeolite molecular sieve and a first solvent, wherein the first solvent is at least one of N-methylpyrrolidone, propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate; the zeolite molecular sieve is at least one of ZSM-5, titanium silicalite, SAPO-34, MCM-22, MOR, SSZ-13, MCM-48, SAPO-5, and SBA-15.
[0027] In some specific embodiments, the mass ratio of the zeolite molecular sieve to the first solvent is 10-25:75-90. In exemplary examples, it can be 10:75, 20:75, 25:75, 10:80, 10:85, 10:90, 20:80, 25:90, and other typical but non-limiting mass ratios or ranges between the two amounts.
[0028] In some specific embodiments, the polymer fluorinated polymer solution includes a polymer fluorinated polymer and a second solvent; the second solvent is N,N-dimethylformamide, dimethyl sulfoxide, N,N-dimethylacetamide, triethyl phosphate, acetone, and dioxane; the polymer fluorinated polymer includes at least one of PTFE (polytetrafluoroethylene), FEP (fluorinated ethylene propylene copolymer), PFA (fusible polytetrafluoroethylene), PVDF (polyvinylidene fluoride) and EPTFE (expanded polytetrafluoroethylene).
[0029] In some specific embodiments, the mass ratio of the high molecular weight fluorinated polymer to the second solvent is 2-5:95-98. In exemplary examples, it can be 2:95, 2:96, 2:98, 3:95, 3:8, 5:95, 5:96, 5:98, etc., which are typical but non-limiting mass ratios or ranges between the two amounts.
[0030] In a second aspect, the present invention provides a method for preparing a negative electrode protective layer, comprising the following steps: Under a protective atmosphere, the zeolite molecular sieve and the first solvent are stirred at room temperature to obtain a zeolite molecular sieve dispersion, and the high molecular weight fluorinated polymer and the second solvent are stirred at room temperature to obtain a high molecular weight fluorinated polymer solution (mechanical stirring may be preferred).
[0031] The zeolite molecular sieve dispersion and the high molecular fluorine-containing polymer solution are electrostatically coaxially spun on the lithium surface. After the spinning is completed, it is vacuum dried to obtain an in-situ formed negative electrode protective layer. The metal lithium surface is modified by electrostatic spinning technology, and then reacts with metal lithium to form LiF to obtain an artificial hybrid protective layer for the metal lithium negative electrode. The metal lithium negative electrode protection material is modified on the surface of the metal lithium negative electrode by electrostatic spinning. Modification by electrostatic spinning technology can form a cross-linked network structure to increase the specific surface area and promote Li + Homogenize deposition and effectively improve the uniformity of the protective layer.
[0032] In some specific embodiments, the stirring speed is 300-800 rpm and the time is 2-4 h.
[0033] In some specific embodiments, the conditions for electrostatic coaxial convection spinning are: The electrospinning spray solution feed rate of zeolite molecular sieve dispersion was 0.4 mL·h -1 ~0.6 mL·h -1 , the applied voltage is 22-25kV, the distance between the spinneret tip and the current collector is 15cm-20cm, the temperature is 26℃, and the relative humidity is 35%; The electrospinning rate of the fluorinated polymer solution was 0.6 mL·h. -1 ~ 0.9 mL·h -1 , the applied voltage was 25-28 kV, the distance between the spinneret tip and the current collector was 15 cm~20 cm, the temperature was 26°C, and the relative humidity was 35%.
[0034] Furthermore, the protective atmosphere is formed by a protective gas, and the protective gas is one of an inert gas and nitrogen, but is not limited thereto, and the reaction only needs to be carried out in a protective atmosphere.
[0035] In a third aspect, the present invention provides a negative electrode for a lithium battery, wherein the negative electrode for the lithium battery comprises the negative electrode protective layer described above.
[0036] In a third aspect, the present invention provides a lithium battery, comprising the above-mentioned lithium battery negative electrode.
[0037] The mechanism of action of the metal lithium negative electrode protection material provided by the present invention on the lithium metal negative electrode is that the cross-linked mesh protective layer formed by electrospinning has a larger specific surface area and better uniformity, and at the same time, it has abundant nanochannels and a larger specific surface area in the zeolite molecular sieve. The abundant acid sites on the skeleton can anchor anions through acid-base interactions, thereby selectively allowing Li + Rapid migration and uniform Li deposition at the electrode interface. The high molecular weight fluorinated polymer has excellent flexibility and a large amount of fluorine, which can form a stable LiF protective layer to maintain the mechanical and dimensional stability of the protective layer to the liquid electrolyte during the cycle, allowing lithium to be uniformly deposited at a high deposition capacity. In addition, the flexibility of the hybrid artificial protective layer can adapt to the volume change of lithium metal during repeated plating / stripping, thereby achieving a lithium dendrite-free growth state.
[0038] The present invention adopts the above-prepared lithium metal battery negative electrode can be directly used as a high-energy-dendritic lithium metal battery with high coulombic efficiency. Correspondingly, another aspect of the embodiment of the present invention also provides a high-energy-density lithium metal battery, including a positive electrode material, a negative electrode material, and an electrolyte, wherein the lithium metal battery adopts the above-mentioned lithium metal battery negative electrode.
[0039] In summary, the metal lithium negative electrode protection material provided by the present invention has a high modulus and excellent flexibility, and is applied to the negative electrode of lithium metal to generate a high-performance lithium-philic artificial hybrid protective layer, which can isolate lithium metal and electrolyte, achieve protection of the lithium metal electrode and uniform deposition of lithium ions, and inhibit the growth of dendrites. The lithium metal electrode has high ion conductivity and good stability, which prolongs the life of the lithium metal battery and improves the cycle performance of the lithium metal battery.
[0040] The following is further described in conjunction with specific embodiments.
[0041] Example 1
[0042] Weigh 0.5 g of ZSM-5 and put it into 4.5 g of N-methylpyrrolidone and stir it at room temperature for 1 h to obtain a zeolite dispersion. Weigh 0.1 g of PVDF and put it into 4.9 g of N,N-dimethylformamide solution and stir it at room temperature for 2 h to obtain a high molecular weight fluorinated polymer solution. The electrospinning parameters of the zeolite dispersion were set to a spray solution feed rate of 0.4 mL h -1; The applied voltage was 22 kV; The distance between the spinneret tip and the current collector was 15 cm; The temperature was 26 °C; The relative humidity was 35%; The electrospinning parameters of the polymer fluorinated polymer solution were set to a feed rate of 0.6 mL·h -1 ; The applied voltage is 25kV; The distance between the spinneret tip and the current collector is 15 cm; The temperature is 26℃; The relative humidity is 35%; After the zeolite dispersion and the high molecular fluorine-containing polymer solution are coaxially convectively spun, after the surface modification of the metal lithium is completed, it is placed in a vacuum oven for vacuum drying at room temperature for 2 hours to obtain a uniformly distributed protective layer; Subsequently, the modified metal lithium negative electrode surface will react with the electrospinning layer to form a LiF protective layer in situ, that is, a uniformly distributed artificial hybrid layer is obtained. Finally, the metal lithium electrode with the artificial hybrid layer SEI (negative electrode protective layer) with low toughness and low ion conductivity is obtained. According to the electrochemical test, the metal lithium negative electrode material has a high resistance and a low ion migration number, and shows general metal lithium reversible use in a single-chip battery matched with NCM811. The specific performance results are shown in Table 1.
[0043] Example 2
[0044] Weigh 0.5 g of titanium silicalite molecular sieve and put it into 4.5 g of propylene carbonate and stir it at room temperature for 1 h to obtain a zeolite dispersion. Weigh 0.1 g of PTFE and put it into 4.9 g of dimethyl sulfoxide solution and stir it at room temperature for 2 h to obtain a high molecular weight fluorinated polymer solution. The electrospinning parameters of the zeolite dispersion were set to a spray solution feed rate of 0.4 mL·h -1 ; The applied voltage was 22 kV; The distance between the spinneret tip and the current collector was 15 cm; The temperature was 26 °C; The relative humidity was 35%; The electrospinning parameters of the polymer fluorinated polymer solution were set to a feed rate of 0.6 mL·h -1 ; The applied voltage is 25kV; The distance between the spinneret tip and the current collector is 15 cm; The temperature is 26℃; The relative humidity is 35%; After the surface modification of the metal lithium is completed, it is placed in a vacuum oven for vacuum drying at room temperature for 2 h to obtain a uniformly distributed protective layer; Subsequently, the modified metal lithium negative electrode surface will react with the electrospinning layer to form a LiF protective layer in situ, that is, a uniformly distributed artificial hybrid layer is obtained. Finally, the metal lithium electrode with low toughness and low ion conductivity artificial hybrid SEI (negative electrode protective layer) is obtained. According to the electrochemical test, the metal lithium negative electrode material has a low resistance and a high ion migration number, and shows excellent reversible use of metal lithium in a monolithic battery matched with NCM811. The specific performance results are shown in Table 1.
[0045] Example 3
[0046] Weigh 1 g of MCM-22 into 4 g of dimethyl carbonate and stir at room temperature for 2 h to obtain a zeolite dispersion. Weigh 0.15 g of FEP into 4.85 g of triethyl phosphate solution and stir at room temperature for 2 h to obtain a high molecular weight fluorinated polymer solution. The electrospinning parameters of the zeolite dispersion were set to a spray solution feed rate of 0.5 mL·h -1 ; The applied voltage was 23 kV; The distance between the spinneret tip and the current collector was 17 cm; The temperature was 26 °C; The relative humidity was 35%; The electrospinning parameters of the polymer fluorinated polymer solution were set to a feed rate of 0.8 mL·h -1 ; The applied voltage is 26 kV; The distance between the spinneret tip and the current collector is 18 cm; The temperature is 26°C; The relative humidity is 35%; After the surface modification of the metal lithium is completed, it is placed in a vacuum oven for vacuum drying at room temperature for 2 h to obtain a uniformly distributed protective layer; Subsequently, the modified metal lithium negative electrode surface will react with the electrospinning layer to form a LiF protective layer in situ, that is, a uniformly distributed artificial hybrid layer is obtained. Finally, the metal lithium electrode with high toughness and high ion conductivity artificial hybrid SEI (negative electrode protective layer) is obtained. According to the electrochemical test, the metal lithium negative electrode material has a low resistance and a high ion migration number, and shows excellent reversible use of metal lithium in a single-chip battery matched with NCM811. The specific performance results are shown in Table 1.
[0047] Comparative Example 1
[0048] A method for preparing an unmodified metallic lithium electrode comprises the following steps: The stacked single-chip soft-pack battery was injected with a commercial electrolyte (carbonate electrolyte) for cycle testing. The metal lithium negative electrode material obtained from the electrochemical test had a higher resistance and a lower ion migration number, and exhibited poor reversible use of metal lithium in a single-chip battery matched with NCM811. The specific performance results are shown in Table 1.
[0049] Comparative Example 2
[0050] A method for preparing a modified metallic lithium electrode comprises the following steps: Weigh 0.5 g of titanium silicalite molecular sieve and put it into 4.5 g of propylene carbonate and stir it at room temperature for 2 h to obtain a zeolite dispersion. The electrospinning parameters of the zeolite dispersion were set to a spray solution feed rate of 0.4 mL·h -1; The applied voltage is 22 kV; The distance between the spinneret tip and the current collector is 15 cm; The temperature is 25°C; The relative humidity is 35%; After the electrospinning modification is completed, it is placed in a vacuum oven for vacuum drying at room temperature for 1 h to obtain a uniformly distributed modification layer, and finally the metal lithium electrode with high Young's modulus and fast ion conduction artificial SEI (negative electrode protective layer) is obtained. The stacked single-chip soft-pack battery is injected with a commercial electrolyte (carbonate electrolyte) for cycle testing. According to the electrochemical test, the metal lithium negative electrode material has a higher resistance and a lower ion migration number, and exhibits poor metal lithium reversible use in a single-chip battery matching NCM811; The specific performance results are shown in Table 1.
[0051] Comparative Example 3
[0052] A method for preparing a modified metallic lithium electrode comprises the following steps: Weigh 0.05 g of PVDF and put it into 4.95 g of N,N-dimethylformamide solution, and stir it magnetically at room temperature for 2 h to obtain a high molecular weight fluorinated polymer solution. The electrospinning parameters of the high molecular weight fluorinated polymer solution were set to a spray solution feed rate of 0.4 mL·h -1 ; The applied voltage is 22kV; The distance between the spinneret tip and the current collector is 15 cm; The temperature is 25℃; The relative humidity is 35%; After the surface modification of the metal lithium is completed, it is placed in a vacuum oven for vacuum drying at room temperature for 1 hour to obtain a uniformly distributed modification layer, and finally the metal lithium electrode with high toughness and low ion conductivity artificial organic layer SEI (negative electrode protective layer) is obtained. The stacked single-chip soft-pack battery is injected with a commercial electrolyte (carbonate electrolyte) for cycle testing. According to the electrochemical test, the metal lithium negative electrode material has high resistance and low ion migration number, and shows poor reversible use of metal lithium in a single-chip battery matching NCM811; The specific performance results are shown in Table 1.
[0053] Table 1
[0054] Battery resistance and t of Examples 1 to 3 and Comparative Examples 1 to 3 (Li+) The cycle performance measurement results are shown in Table 1.
[0055] The electron microscope image of the surface of the metal lithium negative electrode protective layer obtained in Example 3 is as follows: Figure 1 As shown, it can be seen that the protective layer is relatively uniform and dense. The cross-sectional electron microscopy image of the metal lithium negative electrode protective layer obtained in Example 3 is as follows Figure 2 As shown, it can be seen that the protective layer is in close contact with the metallic lithium negative electrode and has good lithium affinity.
[0056] By comparing the experimental results of the embodiments and the comparative examples, it can be seen that the negative electrode protective layer of the polymer lithium metal battery with high toughness and fast ion conduction prepared by the present invention can effectively inhibit the formation of lithium dendrites and greatly reduce the side reaction between metallic lithium and the electrolyte.
[0057] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0058] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A negative electrode protective layer, characterized in that: The negative electrode protection layer is a double cross-linked hybrid layer prepared by in-situ reaction of a zeolite molecular sieve dispersion and a high molecular fluorine-containing polymer solution through electrostatic coaxial convection spinning and contacting with a metal lithium negative electrode.
2. A negative electrode protective layer according to claim 1, characterized in that: The thickness of the negative electrode protection layer is 3-6 μm.
3. The negative electrode protective layer according to claim 1, characterized in that: The zeolite molecular sieve dispersion includes zeolite molecular sieve and a first solvent; The first solvent is at least one of N-methylpyrrolidone, propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate; The zeolite molecular sieve is at least one of ZSM-5, titanium silicalite molecular sieve, SAPO-34, MCM-22, MOR, SSZ-13, MCM-48, SAPO-5, and SBA-15.
4. A negative electrode protective layer according to claim 3, characterized in that: The mass ratio of the zeolite molecular sieve to the first solvent is 10-25:75-90.
5. The negative electrode protective layer according to claim 1, characterized in that: The high molecular fluorine-containing polymer solution includes a high molecular fluorine-containing polymer and a second solvent; The second solvent is N,N-dimethylformamide, dimethyl sulfoxide, N,N-dimethylacetamide, triethyl phosphate, acetone, or dioxane; The high molecular weight fluorine-containing polymer includes at least one of PTFE, FEP, PFA, PVDF and EPTFE.
6. A negative electrode protective layer according to claim 5, characterized in that: The mass ratio of the high molecular weight fluorine-containing polymer to the second solvent is 2-5:95-98.
7. A method for preparing a negative electrode protective layer according to any one of claims 1 to 6, characterized in that: The steps include: Under a protective atmosphere, stirring the zeolite molecular sieve and the first solvent at room temperature to obtain a zeolite molecular sieve dispersion, and stirring the high molecular weight fluorine-containing polymer and the second solvent at room temperature to obtain a high molecular weight fluorine-containing polymer solution; The zeolite molecular sieve dispersion and the high molecular weight fluorine-containing polymer solution are electrostatically coaxially spun on the lithium surface. After the spinning is completed, vacuum drying is performed to obtain an in-situ formed negative electrode protective layer.
8. The method for preparing a negative electrode protective layer according to claim 7, characterized in that: The conditions for electrostatic coaxial convection spinning are: The electrospinning spray solution feed rate of zeolite molecular sieve dispersion was 0.4 mL·h -1 ~0.6 mL·h -1 , the applied voltage is 22-25kV, the distance between the spinneret tip and the current collector is 15cm-20cm, the temperature is 26℃, and the relative humidity is 35%; The electrospinning rate of the fluorinated polymer solution was 0.6 mL·h. -1 ~ 0.9 mL·h -1 , the applied voltage was 25-28 kV, the distance between the spinneret tip and the current collector was 15 cm~20 cm, the temperature was 26°C, and the relative humidity was 35%.
9. A lithium battery negative electrode, characterized in that: The negative electrode protective layer comprises the negative electrode protective layer as described in any one of claims 1 to 6.
10. A lithium battery, characterized in that: Including the lithium battery negative electrode as described in claim 9.
Citation Information
Patent Citations
Negative electrode with surface coated with lithiated zeolite and lithium ion battery using negative electrode
CN103887473A
Modified lithium metal battery negative electrode and preparation method thereof
CN117423919A
Negative plate for lithium-oxygen battery as well as preparation method and application of negative plate
CN117438537A
Composite zinc electrode and preparation method and application thereof
CN117458009A
Battery diagnosis method and battery diagnosis apparatus
KR102766515B1